Application of Good Governance Principles in Improving the Quality of Public Services in Daragdan District, Purwakarta Regency - Setiawan, Heru Dian (HK-Publishing, 2022)
AbstractIn addition to running government, the government is responsible for public service typified by good governance. The implementation of public services is an effort by the state to satisfy the fundamental needs and civil rights of every citizen with respect to administrative services provided by public service providers. Public service is a crucial component of all public institutions, including government agencies. Therefore, government bureaucracy must always prioritize the public interest when providing public services. The purpose of this study is to investigate the Application of Good Governance Principles in Improving the Quality of Public Services. This study employs a qualitative approach and descriptive methodologies. In Daragdan District, the principles of good governance, including community participation, law enforcement, transparency, responsiveness of officers, effectiveness and efficiency of services, and accountability, have been effectively implemented, according to the research findings. Personnel and infrastructural deficiencies still exist in the public services sector.Keywords: Principles, Good Governance, Quality, Public ServiceÂ AbstrakSelain menjalankan pemerintahan, pemerintah bertanggung jawab atas pelayanan publik yang dilambangkan dengan good governance. Penyelenggaraan pelayanan publik merupakan upaya negara untuk memenuhi kebutuhan dasar dan hak-hak sipil setiap warga negara atas pelayanan administratif yang diberikan oleh penyelenggara pelayanan publik. Pelayanan publik merupakan komponen penting dari semua lembaga publik, termasuk lembaga pemerintah. Oleh karena itu, birokrasi pemerintahan harus selalu mengutamakan kepentingan publik dalam memberikan pelayanan publik. Tujuan dari penelitian ini adalah untuk mengetahui Penerapan Prinsip Good Governance dalam Peningkatan Kualitas Pelayanan Publik. Penelitian ini menggunakan pendekatan kualitatif dan metodologi deskriptif. Di Kabupaten Daragdan, prinsip-prinsip tata pemerintahan yang baik, meliputi partisipasi masyarakat, penegakan hukum, transparansi, ketanggapan petugas, efektivitas dan efisiensi pelayanan, dan akuntabilitas, telah dilaksanakan secara efektif, menurut temuan penelitian. Kekurangan personel dan infrastruktur masih ada di sektor layanan publik.Kata Kunci : Prinsip, Good Governance, Kualitas, Pelayanan Publik